2022
DOI: 10.23736/s1973-9087.21.06814-3
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial points treatment with focused extracorporeal shock wave therapy (f-ESWT) for plantar fasciitis: an open label randomized clinical trial

Abstract: The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…O alívio da dor ocorrerá neste caso após meses, provavelmente devido ao tempo necessário para o restabelecimento biológico do tecido e resolução da inflamação. 16 Na fase aguda da lesão, substâncias inflamatórias estão presentes em excesso o que torna o tecido hipersensibilizado. Esta fase pode durar entre 5 e 15 dias.…”
Section: Resultsunclassified
“…O alívio da dor ocorrerá neste caso após meses, provavelmente devido ao tempo necessário para o restabelecimento biológico do tecido e resolução da inflamação. 16 Na fase aguda da lesão, substâncias inflamatórias estão presentes em excesso o que torna o tecido hipersensibilizado. Esta fase pode durar entre 5 e 15 dias.…”
Section: Resultsunclassified
“…Among the several conservative treatment options for PF, ESWT is considered the gold standard. And PF also happens to be one of the indications with the best results after applying ESWT, along with insertional tendinopathy of the Achilles tendon and mid-portion Achillodynia ( 19 , 20 ). We can learn in a meta-analysis that Fan et al found that moderate energy ESWT (0.12–0.25 mJ/mm2) had similar effects to low energy ESWT (0.06–0.11 mJ/mm2) in improving pain scores in Achilles tendinopathy, suggesting that further studies are needed to determine the optimal energy level for treating Achilles tendinopathy.…”
Section: Comparison Of the Clinical Efficacy Of Eswt In Different Com...mentioning
confidence: 99%
“…Because of its economy and effectiveness, it has gradually become a very essential means of rehabilitation medicine in recent years. ESWT has been used to treat a variety of conditions, including musculoskeletal injuries, such as plantar fasciitis [ 3 ] and tennis elbow [ 4 , 5 ], as well as some neurological conditions [ 6 , 7 ]. The technology has developed rapidly in recent years, with the introduction of more advanced equipment and improved understanding of the underlying mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%